A Pseudo-outbreak of Aspergillosis at a Tertiary Care Hospital: Thinking Beyond the Infection Control Risk Assessment. (11th October 2016) - Doll, Michelle; Preas, Michael Anne; Johnson, J. Kristie; Mitchell, Clifford; Roup, Brenda; Wilson, Lucy; Carothers, Christine; Nkonge, Grace; Leekha, Surbhi
Abstract : In the modern era of carefully monitored renovations, construction-related Aspergillus outbreaks have decreased. We investigated an increase in clinical cultures growing Aspergillus species, determining that contamination of the mycology lab caused a pseudo-outbreak. A major construction site was appropriately sealed, but unrecognized staff traffic may have facilitated laboratory contamination. Infect Control Hosp Epidemiol 2016;1–4